2011
DOI: 10.1590/s1677-04202011000300005
|View full text |Cite
|
Sign up to set email alerts
|

Changes in growth, pigment content and antioxidants in the root and leaf tissues of wheat plants under the influence of exogenous salicylic acid

Abstract: The effect of various concentrations of salicylic acid (SA) on the growth, pigment content and the activity of antioxidants was investigated in the laboratory grown wheat plants. The root and shoot growth was affected at higher concentration of SA in early days of growth. The activities of catalase (CAT), ascorbate peroxidase (APX) and guaicol-specific peroxidase (POX) declined with the application of SA (50, 500 and 1000 µM), the decrease being more pronounced with the increase in SA concentrations both in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 34 publications
2
17
2
Order By: Relevance
“…Supplementing SA or ABA to the medium (PEG + SA or PEG + ABA) caused a decrease of these seedling parameters for both cultivars. Similar observations were presented in a study by Sahu and Sabat [15], where SA was added to the culture of wheat seedlings in the early stage of growth under salinity stress conditions. ABA application significantly decreased dry shoot biomass and significantly increased leaf mass per area, root/shoot ratio, and fine root/total root ratio in Picea asperata [39].…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Supplementing SA or ABA to the medium (PEG + SA or PEG + ABA) caused a decrease of these seedling parameters for both cultivars. Similar observations were presented in a study by Sahu and Sabat [15], where SA was added to the culture of wheat seedlings in the early stage of growth under salinity stress conditions. ABA application significantly decreased dry shoot biomass and significantly increased leaf mass per area, root/shoot ratio, and fine root/total root ratio in Picea asperata [39].…”
Section: Resultssupporting
confidence: 87%
“…PEG + ABA treatment caused a further increase of this parameter for susceptible SQ1 while it remained on the same level for resistant CS. Similarly, in investigations by Sahu and Sabat [15], it was noticed that exogenously applied SA increased MDA content in wheat plants, though only when applied in higher concentration. They concluded that SA in low concentration can regulate the activities of intracellular antioxidant enzymes and increase plant tolerance to environmental stresses.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…Erythromycin can affect the membrane system; changes in MDA content can be used to gauge this effect. MDA is a peroxidation product of fatty acids of membrane lipids and is commonly considered as an important index of lipid peroxidation to reflect cellular oxidative damage under environmental stress [46,47]. In this study, the MDA contents were significantly higher in high erythromycin concentration treatments compared to the control, indicating that high erythromycin concentrations induced stronger peroxidation and caused more serious damage to the cell membrane.…”
Section: Discussionmentioning
confidence: 56%